Memorial to the Minister of Health - Loat, Lily (London : National Anti-Vaccination League)
1928-11-30 1928 1920s 8 pages The above figures show that 85 per cent. of the cases brought under the notice of the Andrewes Committee and at least 72 per cent. of the cases brought under the notice of the Rolleston Committee had been vaccinated with Government lymph, and, as the latter Committee estimate that only 60 per cent. of the vaccinations in the country are performed by public vaccinators, it would appear that the incidence of cases was greater in the case of publicly-vaccinated persons than in the case of those not so vaccinated. Possibly the difference may be due to the fact that a relatively larger proportion of cases were brought to the notice of the Committees by public vaccinators than by private vaccinators. Even supposing that the cases summarised above were all the cases which occurred (and the Committee themselves admit that the information obtained cannot be regarded as being an index of the real prevalence of the condition) we feel compelled to take strong exception to the suggestion made, or endorsed, by both Committees that the risk of such cases is of a rare character. The method adopted in order to arrive at this conclusion (namely, a comparison of the post-vaccinal encephalitis cases with the number of vaccinations performed) is, we submit, an altogether wrong method. The prime object of vaccination is to prevent persons being fatally attacked by smallpox. The risks to be compared, therefore, would be those of death from post-vaccinal encephalitis with those of death from smallpox, in children under 15 years of age. When this is done the following result appears :— Deaths of Children under 15 years of age from— Post-vaccinal encephalitis. Smallpox 1922 (1 month only) 6 5 1923 24 3 1924 — 5 1925 4 2 1926 1 7 1927 (9 months only) 7 23* Total for 58 months 42 Total for 72 months 45 * Assuming all these to be smallpox deaths. The Medical Officer’s Annual Report for 1927 shows that some were certainly not. Incomplete as they are, these figures suffice to show that there was just as great a risk of a child dying from post-vaccinal encephalitis in those years as from smallpox : in fact, there is good ground for believing that the risk was far greater seeing that the steps taken by both Committees to obtain knowledge of such cases were not adequate to secure the end in view. Of the 63 cases dealt with in the Andrewes Report, 53 were under 15 years of age. 29 of them died and 24 were non-fatal. The subsequent history of 10 of the non-fatal cases was traced ; 6 had completely recovered ; 4 had the mind permanently injured. These 4 might well be added to the fatal cases as equally disastrous. The Andrewes Committee depended almost entirely upon the information gathered in a casual way by the Medical Inspectors of your Department. The Rolleston Committee made a wider appeal, but in both cases the efforts made were not likely to lead to complete returns. The doctors making such returns would be practically convicting themselves of having wrongly diagnosed the cases in the first instance. Few doctors would be likely to do this, particularly when they knew that the Committees wished to be able to make out a case which would not incriminate vaccination. What, we submit, the Committees should have done was, through you, to instruct all doctors to note on certificates in respect of all deaths occurring within three months after vaccination the fact that vaccination had been performed and the date of such vaccination. Particulars of these deaths could then have been obtained from the various Registrars and any inquiries deemed necessary by the Committee could have been made. It is not too late even now (as such deaths are still occurring) for some such regulation to be framed and we suggest it for your consideration. Every Medical Officer of Health could have been required to 2 292/840/1/13